A Randomized Waitlist-Controlled Trial of an Intergenerational Arts and Heritage-Based Intervention in Singapore: Project ARTISAN - Ho, Andy Hau Yan; Ma, Stephanie Hilary Xinyi; Tan, Michael Koon Boon; Bajpai, Ram Chandra (Frontiers in Psychology, 2021)
Loneliness has become a global major public health concern, with detrimental effects to the young and old. ARTISAN (Aspiration and Resilience Through Intergenerational Storytelling and Art-based Narratives) is a 5-week, 15-h participatory art and group-based intervention that focuses on resilience building and loneliness alleviation among the young and old through a structured multimodal framework held at a museum space. Developed with a Participatory Action Research (PAR) approach, this intervention is evaluated using an open-label waitlist randomized controlled trial design (RCT) comprised of community-dwelling youth and older adults randomized into an intervention group (n = 35) or a waitlist-control group (n = 33). Participants were assessed on standardized self-reported psychometric measures including loneliness, resilience, quality of life, social support, life satisfaction and national identity at three time points. Qualitative data generated during each intervention session as well as acceptability focus groups were recorded and transcribed. Linear mixed modeling analyses revealed that participants in the intervention group experienced improvements in life satisfaction compared to participants in the waitlist-control group (95% CI: 0.22 to 0.77, p < 0.001, Cohen's d = 0.53) immediately after the completion of ARTISAN. Subgroup analyses for youth participants indicated improvements in quality of life (95% CI: 0.16 to 0.52, p < 0.001, d = 1.31) and national identity (95% CI: 0.18 to 0.80, p = 0.002, d = 0.43) in comparison to the waitlist-control group. At 5-weeks follow-up, the intervention group participants continued to experience high levels of life satisfaction (95% CI: 0.04 to 0.42, p = 0.017, d = 0.47), enhancements in resilience (95% CI: 0.07 to 0.55, p = 0.011, d = 0.46), as well as a significant reduction in loneliness (95% CI: −0.34 to −0.08, p = 0.001, d = 0.61) compared to baseline, reflecting the effectiveness and positive residual effects of the ARTISAN intervention. Similarly, the qualitative findings provided support for the intervention and additional insights to the quantitative findings. This holistic intervention framework that integrates stories, arts and heritage for bridging and empowering lives fills a critical gap in knowledge and practice between the arts, health and citizenship, paving the way for further research in creating a more caring and inclusive society with the arts. Clinical Trials Registration:www.ClinicalTrials.gov, identifier: NCT03048708.